Morphology and kinematics of the ionised gas in early-type galaxies - Falcon-Barroso, J; Sarzi, M; Bacon, R; Bureau, M; Cappellari, M; Davies, R; Emsellem, E; Fathi, K; Krajnovic, D; Kuntschner, H; McDermid, R; Peletier, R; et al. (2006)
We present results of our ongoing study of the morphology and kinematics of the ionised gas in 48 representative nearby elliptical and lenticular galaxies using the SAURON integral-field spectrograph on the 4.2m William Herschel Telescope. Making use of a recently developed technique, emission is detected in 75% of the galaxies. The ionised-gas distributions display varied morphologies, ranging from regular gas disks to filamentary structures. Additionally, the emission-line kinematic maps show, in general, regular motions with smooth variations in kinematic position angle. In most of the galaxies, the ionised-gas kinematics is decoupled from the stellar counterpart, but only some of them present signatures of recent accretion of gaseous material. The presence of dust is very common in our sample and is usually accompanied by gas emission. Our analysis of the [Om]/H beta emission-line ratios, both across the whole sample as well as within the individual galaxies, suggests that there is no unique mechanism triggering the ionisation of the gas. (c) 2005 Elsevier B.V. All rights reserved.